Reading Of The Foundational Project Of The Absurd Cognitive Story Of The Critic And Creator Salah Ghilous - ouahab, khaled (El Omda in Linguistics and Discourse Analysis, 2024)
This reading takes its legitimacy by asking questions targeting the founding concept of this project and others targeting the conditions and rules of writing and the mechanisms of analysis of this new literary genre, of course, in light of what was mentioned in the founding article: The absurd cognitive story from experimentation to the establishment of the critic and creator Salah Ghilous. This reading never claims to be going to provide definitive answers, it only seeks to open paths that illuminate an aspect of this project.